5, 5, 15, 15‐Tetraoxo‐5, 15‐Dithiaporphyrin as a Highly Electron‐Deficient Porphyrinic Ligand. Issue 68 (4th November 2019) - Yagi, Atsumi; Kondo, Takeshi; Yamashita, Daisuke; Wachi, Naruhiko; Omori, Hiroto; Fukui, Norihito; Ikeue, Takahisa; Shinokubo, Hiroshi
Abstract: Oxidation of 5, 15‐dithiaporphyrin with meta ‐chloroperbenzoic acid afforded the corresponding S, S ‐tetraoxide in good yield. The resultant 5, 5, 15, 15‐tetraoxo‐5, 15‐dithiaporphyrin exhibited the highly electron‐deficient nature as elucidated by the electrochemical analysis and theoretical calculations. Treatment of tetraoxodithiaporphyrin with zinc(II) acetate and nickel(II) acetate provided the corresponding metal complexes efficiently. Owing to its enhanced Lewis acidity of the metal center by the electron‐deficient ligand, the nickel complex underwent facile axial ligation to form pentacoordinate and hexacoordinate high‐spin ( S= 1) complexes in solution and solid, respectively. The binding constant of pyridine to the Ni II center was significantly higher than those of conventional porphyrin Ni II complexes. Temperature‐dependent magnetic susceptibility measurements of the high‐spin Ni II complex revealed the presence of weak ferromagnetic interactions. Abstract : Macro binding : 5, 5, 15, 15‐Tetraoxo‐5, 15‐dithiaporphyrin has been prepared by oxidation of 5, 15‐dithiaporphyrin, which served as a highly electron‐deficient tetrapyrrolic macrocyclic ligand. Owing to its enhanced Lewis acidity, the low‐spin ( S= 0) nickel complex strongly binds axial ligands to yield high‐spin ( S= 1) complexes in solution and in the solid state.